2017
DOI: 10.1177/1049732317726761
|View full text |Cite
|
Sign up to set email alerts
|

A Transcription and Translation Protocol for Sensitive Cross-Cultural Team Research

Abstract: Assurance of transcript accuracy and quality in interview-based qualitative research is foundational for data accuracy and study validity. Based on our experience in a cross-cultural ethnographic study of women’s pelvic organ prolapse, we provide practical guidance to set up step-by-step interview transcription and translation protocols for team-based research on sensitive topics. Beginning with team decisions about level of detail in transcription, completeness, and accuracy, we operationalize the process of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 38 publications
(66 reference statements)
0
55
0
Order By: Relevance
“…Conceptual translation between languages and cultures is recognised to be an issue in both qualitative and quantitative research (Clark 2017; Al‐Amer 2015; Stevelink 2013). Regmi 2010 discusses the issues of translation (a direct and literal word‐for‐word process) and transliteration (a process of translating meaning which may not be word‐for‐word) in undertaking qualitative research in different language and cultural groups.…”
Section: Methodsmentioning
confidence: 99%
“…Conceptual translation between languages and cultures is recognised to be an issue in both qualitative and quantitative research (Clark 2017; Al‐Amer 2015; Stevelink 2013). Regmi 2010 discusses the issues of translation (a direct and literal word‐for‐word process) and transliteration (a process of translating meaning which may not be word‐for‐word) in undertaking qualitative research in different language and cultural groups.…”
Section: Methodsmentioning
confidence: 99%
“…Identifying information such as pastor names were removed or abbreviated and Spanish transcripts were translated to English using standard protocols. 59 To ensure all aspects of the qualitative research was reported, the consolidated criteria for reporting qualitative studies (COREQ) 60 was used as a checklist (see Additional file 2).…”
Section: Data Collectionmentioning
confidence: 99%
“…The Spanish language focus groups will be transcribed in Spanish and then translated into English using best practices to assure accuracy in translation (Clark, Birkhead, Fernandez, & Egger, ). Briefly, a native Spanish‐speaking moderator and the translator will review all original and translated transcripts.…”
Section: Qualitative Data Management Analysis and Interpretationmentioning
confidence: 99%
“…The Spanish language focus groups will be transcribed in Spanish and then translated into English using best practices to assure accuracy in translation (Clark, Birkhead, Fernandez, & Egger, 2017).…”
Section: Data Managementmentioning
confidence: 99%